The Aspergillus nidulans syntaxin PepAPep12 is regulated by two Sec1/Munc‐18 proteins to mediate fusion events at early endosomes, late endosomes and vacuoles. Issue 1 (26th October 2015) - López‐Berges, Manuel S.; Pinar, Mario; Abenza, Juan F.; Arst, Herbert N.; Peñalva, Miguel A.
Summary: Syntaxins are target‐SNAREs that crucially contribute to determine membrane compartment identity. Three syntaxins, Tlg2p, Pep12p and Vam3p, organize the yeast endovacuolar system. Remarkably, filamentous fungi lack the equivalent of the yeast vacuolar syntaxin Vam3p, making unclear how these organisms regulate vacuole fusion. We show that the nearly essential A spergillus nidulans syntaxin PepA Pep12, present in all endocytic compartments between early endosomes and vacuoles, shares features of Vam3p and Pep12p, and is capable of forming compositional equivalents of all known yeast endovacuolar SNARE bundles including that formed by yeast Vam3p for vacuolar fusion. Our data further indicate that regulation by two Sec1/Munc‐18 proteins, Vps45 in early endosomes and Vps33 in early and late endosomes/vacuoles contributes to the wide domain of PepA Pep12 action. The syntaxin TlgB Tlg2 localizing to the TGN appears to mediate retrograde traffic connecting post‐Golgi (sorting) endosomes with the TGN. TlgB Tlg2 is dispensable for growth but becomes essential if the early Golgi syntaxin SedV Sed5 is compromised, showing that the Golgi can function with a single syntaxin, SedV Sed5 . Remarkably, its pattern of associations with endosomal SNAREs is consistent with SedV Sed5 playing roles in retrograde pathway(s) connecting endocytic compartments downstream of the post‐Golgi endosome with the Golgi, besides more conventional intra‐Golgi roles. Abstract : A duplication of an ancestral endovacuolar SNARE generated two specialized syntaxins in the Saccharomyces cerevisiae lineage: Pep12p and Vam3p, acting on endosomes and vacuoles, respectively. This duplication did not occur in the Pezizomycotina including Aspergillus nidulans, in which a single syntaxin, PepA Pep12, mediates membrane fusion at early endosomes, late endosomes and vacuoles, i.e. at all levels of the endocytic pathway excepting sorting endosomes, where fusion is regulated by the syntaxin TlgB.